Powder for laminate molding

By controlling the particle size distribution of the powder for lamination molding and the combination of inorganic oxide powder, the problems of uneven material distribution and high sintering shrinkage in the adhesive spraying method are solved, and a three-dimensional lamination molding with uniform laying and low shrinkage are achieved. body.

CN119317614AActive Publication Date: 2025-01-14RESONAC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380044390.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-26
Filing Date
2023-12-20
Publication Date
2025-01-14
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

In the adhesive spraying method, the problem of uneven distribution of voids and materials often occurs in the three-dimensional layered molding body, and the fluidity and volume density of the powder layer are difficult to take into account, and the shrinkage rate is high during sintering.

Method used

By controlling the particle size distribution of the powder for lamination molding, especially the ratio of D10, D50 and D90, and combining with the combination of inorganic oxide powders of different particle sizes, powders with moderate fluidity and volume density are prepared to ensure that the adhesive can be uniform Enter and reduce shrinkage upon sintering.

Benefits of technology

The uniform laying and high-density filling of the powder layer are achieved, the shrinkage rate during sintering is reduced, and the permeability of the adhesive and the density of the laminated molding are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164575940000151
    Figure BDA0005164575940000151
  • Figure BDA0005164575940000161
    Figure BDA0005164575940000161
  • Figure BDA0005164575940000171
    Figure BDA0005164575940000171
Patent Text Reader

Abstract

A powder for laminate molding, which is an inorganic oxide powder and has a D10 of 1.0 to 4.0 [mu] m, a D50 of 5.5 to 9.0 [mu] m, a D90 of 20.0 to 40.0 [mu] m, and a volume ratio of particles having a particle diameter of 16.8 to 60.0 [mu] m of 15.0 to 22.0 vol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a powder for laminated molding, a sintered body thereof, and a method for producing a binder-injected laminated molding body. Background Art

[0002] In recent years, processing methods such as additive manufacturing (AM) technology and 3D printing technology have attracted attention. This is a technology that produces a cross-sectional shape based on the data of the three-dimensional shape of the target body and stacks it to obtain the target body. As additive manufacturing technology, known processing methods include: a binder jet method (Patent Document 1) in which a binder is sprayed onto a powder material on a modeling table to selectively shape it; a material jet method (Patent Document 1) in which a photocurable resin is sprayed from an inkjet nozzle to selectively shape it; a powder bed melting method (Patent Document 2) in which a powder bed covered with metal powder is irradiated with a laser or electron beam to selectively melt it to shape it; and a photoforming method (Patent Document 2) in which a slurry mixed with a liquid photocurable resin and an inorganic powder is irradiated with light to shape it.

[0003] Prior Art Literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-117069

[0006] Patent Document 2: Japanese Patent Application Publication No. 2021-11050 Summary of the invention

[0007] The binder jetting method is also known by the term "3D inkjet powder printing". This method includes, for example, a process of supplying powder material to a molding table using a roller to form a uniform powder layer; and a process of applying a liquid binder to the powder layer through an inkjet print head to selectively combine a part of the powder layer. By repeating these processes, a three-dimensional stacked molding body as the target can be obtained. Then, the three-dimensional stacked molding body is sintered as needed. In the binder jetting method, sometimes a structure in which the distribution of the constituent materials such as voids is unevenly generated in the obtained three-dimensional stacked molding body. In order to suppress this situation, it is desired that the powder for stacking molding has good laying properties that can be smoothly supplied to the molding table and can be evenly spread. In addition, it is believed that by filling the powder for stacking molding with a high density, a three-dimensional stacked molding body with high uniformity can be obtained. In order to achieve good laying properties and high-density filling, it is useful to improve the fluidity of the powder material. On the other hand, when applying the binder, it is also required that the powder layer is not disturbed and the binder can enter between the powder materials. In addition, it is also desired that the shrinkage rate during sintering is low.

[0008] The present disclosure provides a material which, as a powder for stacked modeling, has both good laying properties capable of forming a uniform powder layer and moderate fluidity capable of maintaining shape stability from the application of an adhesive to a sintering process, and has a moderate bulk density capable of allowing the adhesive to enter between powder materials and achieving a low shrinkage rate during sintering.

[0009] The inventors have found that by controlling the volume ratio of particles with relatively large particle sizes in the powder for laminated molding within a specific range, the fluidity and bulk density of the powder for laminated molding can be controlled within an appropriate range. Furthermore, the inventors have found that by mixing two kinds of inorganic oxide powders with different particle size distributions at a predetermined ratio, the fluidity and bulk density of the powder material can be controlled within an appropriate range.

[0010] The contents of this disclosure relate to the following matters.

[0011] [1] A powder for laminated modeling, which is an inorganic oxide powder,

[0012] D10 is 1.0~4.0μm, D50 is 5.5~9.0μm, D90 is 20.0~40.0μm,

[0013] The volume ratio of particles having a particle size of 16.8 to 60.0 μm is 15.0 to 22.0% by volume.

[0014] [2] The powder for laminated molding according to [1], wherein the volume ratio of particles having a particle size of 2.0 μm or more is 90.0 to 100 volume %.

[0015] [3] The powder for laminated molding according to [1] or [2],

[0016] The ratio of D50 to D10 (D50 / D10) is 2.0 to 2.2.

[0017] The ratio of D90 to D10 (D90 / D10) is 6.0 to 8.0.

[0018] [4] The powder for laminated molding according to any one of [1] to [3], wherein the BET specific surface area is 0.1 to 10.0 m 2 / g.

[0019] [5] The powder for laminated modeling according to any one of [1] to [4], which is spherical in shape.

[0020] [6] The powder for laminated modeling according to any one of [1] to [5], which is aluminum oxide.

[0021] [7] The powder for laminated molding according to [6], wherein the bulk density of the pressed powder under a pressure of 98 MPa is 2.52 to 2.54 g / cm 3 .

[0022] [8] The powder for laminated modeling according to any one of [1] to [7], which is used in a binder spraying method.

[0023] [9] A sintered body, which is a sintered body of the powder for laminated modeling according to any one of [1] to [7].

[0024]

[10] A method for producing a three-dimensional stacked modeling body by binder injection, comprising: applying a liquid containing a binder to the stacked modeling powder described in any one of [1] to [7] to form a three-dimensional stacked modeling body.

[0025]

[11] A method for producing a sintered body, comprising:

[0026] Applying a liquid containing a binder to the layered modeling powder described in any one of [1] to [7] to form a three-dimensional layered modeling body; and

[0027] The three-dimensional stacked shaped body is sintered.

[0028]

[12] A powder for laminated modeling, comprising:

[0029] A coarse-grained inorganic oxide powder (A) having a D50 of 9.0 to 25.0 μm; and

[0030] The fine-particle inorganic oxide powder (B) has a smaller D50 than the coarse-particle inorganic oxide powder (A),

[0031] The volume ratio of the coarse-grained inorganic oxide powder (A) is 9.5 to 29.0 volume % relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B).

[0032]

[13] The powder for laminated molding according to

[12] , wherein the particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 0.26 to 1.15.

[0033]

[14] The powder for laminated molding according to

[12] or

[13] , wherein the D50 (D A 50) and the D50 (D B 50) Satisfy D A 50-D B 50≥3.5μm.

[0034]

[15] A powder for laminated modeling, comprising:

[0035] A coarse-grained inorganic oxide powder (A) having a D50 of 9.0 to 25.0 μm; and

[0036] The fine-particle inorganic oxide powder (B) has a smaller D50 than the coarse-particle inorganic oxide powder (A),

[0037] The particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 0.26 to 1.15.

[0038]

[16] According to the powder for stacked molding described in

[15] , the volume ratio of the coarse-grained inorganic oxide powder (A) relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) is 9.5 to 29.0 volume %.

[0039]

[17] The powder for laminated molding according to

[15] or

[16] , wherein the D50 (D A 50) and the D50 (D B 50) Satisfy D A 50-D B 50≥3.5μm.

[0040]

[18] The powder for laminated modeling according to any one of

[12] to

[17] , wherein D50 of the fine-particle inorganic oxide powder (B) is 5.0 to 8.0 μm.

[0041]

[19] The powder for laminated molding according to any one of

[12] to

[18] ,

[0042] The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide powder (A) is 1.5 to 3.5,

[0043] The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide powder (A) is 4.0 to 7.0.

[0044]

[20] The powder for laminated modeling according to any one of

[12] to

[19] , wherein the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) are both spherical in shape.

[0045]

[21] The powder for laminated modeling according to any one of

[12] to

[20] , wherein the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) are both aluminum oxide.

[0046]

[22] The powder for laminated molding according to

[21] , wherein the bulk density of the pressed powder under a pressure of 98 MPa is 2.52 to 2.54 g / cm 3 .

[0047]

[23] The powder for laminated modeling according to any one of

[12] to

[22] , which is used in a binder spraying method.

[0048]

[24] A sintered body, which is a sintered body of the powder for layered molding as described in any one of

[12] to

[23] .

[0049]

[25] A method for manufacturing a three-dimensional stacked modeling body using a binder injection molding method, comprising: applying a liquid containing a binder to the stacked modeling powder described in any one of

[12] to

[23] to form a three-dimensional stacked modeling body.

[0050]

[26] A method for producing a sintered body, comprising:

[0051] Applying a liquid containing a binder to the layered modeling powder described in any one of

[12] to

[23] to form a three-dimensional layered modeling body; and

[0052] The three-dimensional stacked shaped body is sintered.

[0053]

[27] an aluminum oxide powder,

[0054] D10 is 1.0~4.0μm, D50 is 5.5~9.0μm, D90 is 20.0~40.0μm,

[0055] The volume ratio of particles having a particle size of 16.8 to 60.0 μm is 15.0 to 22.0% by volume.

[0056]

[28] The alumina powder according to

[27] , wherein the volume ratio of particles having a particle size of 2.0 μm or more is 90.0 to 100 volume %.

[0057]

[29] The aluminum oxide powder according to

[27] or

[28] ,

[0058] The ratio of D50 to D10 (D50 / D10) is 2.0 to 2.2.

[0059] The ratio of D90 to D10 (D90 / D10) is 6.0 to 8.0.

[0060]

[30] The alumina powder according to any one of

[27] to

[29] , wherein the BET specific surface area is 0.1 to 10.0 m 2 / g.

[0061]

[31] The alumina powder according to any one of

[27] to

[30] , which is spherical in shape.

[0062]

[32] The alumina powder according to any one of

[27] to

[31] , wherein the compacted bulk density at a pressure of 98 MPa is 2.52 to 2.54 g / cm 3 .

[0063] According to the present disclosure, a powder for stacking modeling can be provided, which has both good laying properties that can form a uniform powder layer and moderate fluidity that can maintain shape stability from the application of the adhesive to the sintering process, and has a moderate volume density that allows the adhesive to enter between the powder materials and achieve a low shrinkage rate during sintering. DETAILED DESCRIPTION

[0064] Hereinafter, embodiments of the present invention will be described. Note that the embodiments described below are representative examples of the present invention and are not intended to limit the present invention.

[0065] Hereinafter, embodiments of the present invention will be described. Note that the embodiments described below are representative examples of the present invention and are not intended to limit the present invention.

[0066] In this specification, regarding a numerical range, when "~" is used, the values ​​at both ends are the upper limit and the lower limit, respectively, and are included in the numerical range. When there are multiple upper limits or lower limits, a numerical range can be created based on all combinations of the upper limits and the lower limits. Similarly, when there are multiple numerical ranges, another numerical range can be created by individually selecting upper limits and lower limits from these numerical ranges and combining them.

[0067] In this specification, D10, D50 and D90 are the 10% particle size, 50% particle size and 90% particle size in the volume-based cumulative particle size distribution measured using a particle size distribution measuring device based on the electrical resistance method (Beckman Coulter, Multisizer 4) with an aperture size of 100 μm.

[0068] In this specification, the press molding bulk density means the density of a molded body formed by placing a sample in a circular mold frame and pressing it at a specified pressure using a commercially available press. The press molding bulk density is a value that serves as an indicator of the bulk density of a powder layer when a thin layer of powder is formed using a roller or the like.

[0069] In this specification, the angle of repose is a value measured and calculated according to JIS R 9301-2-2: 1999 (Alumina powder - Part 2: Physical property measurement methods - 2: Angle of repose).

[0070] In this specification, the BET specific surface area is a value measured and calculated according to "6.2 Flow method (3.5) Single point method" of JIS R 1626:1996 (Determination of specific surface area of ​​fine ceramic powder by gas adsorption BET method). As a pretreatment, the sample is heated to 180°C, nitrogen is flowed for 20 minutes, and then the measurement is performed using nitrogen as the adsorbent.

[0071] In this specification, the circularity is the average value of the values ​​calculated using the following formula (1) for 5000 particles, where the area of ​​the projection image of the particle is represented by S and the perimeter is represented by L.

[0072] 4πS / L 2 (1)

[0073] In this specification, the volume ratio of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) is a value calculated from the charged mass and true density of the materials as follows. The volume VA of the coarse-grained inorganic oxide powder (A) is calculated from the mass of the blended coarse-grained inorganic oxide powder (A) / the true density of the coarse-grained inorganic oxide powder (A). The volume VB of the fine-grained inorganic oxide powder (B) is calculated from the mass of the blended fine-grained inorganic oxide powder (B) / the true density of the fine-grained inorganic oxide powder (B). Using these values, the volume ratio of the coarse-grained inorganic oxide powder (A) is calculated from VA / (VA+VB), and the volume ratio of the fine-grained inorganic oxide powder (B) is calculated from VB / (VA+VB).

[0074] In this specification, the particle size volume ratio is a value calculated by the following formula (2).

[0075] (Volume ratio of coarse inorganic oxide powder (A)×D50 of coarse inorganic oxide powder (A)) / (Volume ratio of fine inorganic oxide powder (B)×D50 of fine inorganic oxide powder (B)) (2)

[0076] <Layering modeling powder>

[0077] The powder for stacking modeling is an inorganic oxide powder, whose D10 is 1.0 to 4.0 μm, D50 is 5.5 to 9.0 μm, and D90 is 20.0 to 40.0 μm. In the powder for stacking modeling, the volume ratio of particles with a particle size of 16.8 to 60.0 μm is 15.0 to 22.0% by volume. The inventors found that in the powder for stacking modeling with a D50 of 5.5 to 9.0 μm, particles with a particle size of 16.8 to 60.0 μm help to improve the fluidity and bulk density of the powder for stacking modeling. Therefore, it was found that by controlling the volume ratio of particles with a particle size of 16.8 to 60.0 μm within a specific range, a good balance between the fluidity and bulk density of the powder material can be achieved.

[0078] The D50 of the powder for stacking modeling is 5.5 μm or more, preferably 6.0 μm or more, and more preferably 6.5 μm or more. The D50 of the powder for stacking modeling is 9.0 μm or less, preferably 8.5 μm or less, and more preferably 8.0 μm or less. The D50 of the powder for stacking modeling is 5.5-9.0 μm, preferably 6.0-8.5 μm, and more preferably 6.5-8.0 μm. If the D50 of the powder for stacking modeling is 5.5 μm or more, the shape stability of the powder layer formed by the powder for stacking modeling is good, and the shrinkage rate during sintering can be reduced. If the D50 of the powder for stacking modeling is 9.0 μm or less, the bulk density and fluidity can be within an appropriate range.

[0079] The D10 of the powder for stacking modeling is 1.0 μm or more, preferably 2.0 μm or more, and more preferably 3.0 μm or more. The D10 of the powder for stacking modeling is 4.0 μm or less, preferably 3.8 μm or less, and more preferably 3.6 μm or less. The D10 of the powder for stacking modeling is 1.0-4.0 μm, preferably 2.0-3.8 μm, and more preferably 3.0-3.6 μm. If the D10 of the powder for stacking modeling is 1.0 μm or more, the shrinkage rate during sintering can be reduced. If the D10 of the powder for stacking modeling is 4.0 μm or less, the bulk density and fluidity can be within an appropriate range.

[0080] The D90 of the powder for stacking modeling is 20.0 μm or more, preferably 20.5 μm or more, and more preferably 21.0 μm or more. The D90 of the powder for stacking modeling is 40.0 μm or less, preferably 30.0 μm or less, and more preferably 25.0 μm or less. The D90 of the powder for stacking modeling is 20.0-40.0 μm, preferably 20.5-30.0 μm, and more preferably 21.0-25.0 μm. If the D90 of the powder for stacking modeling is 20.0 μm or more, the shape stability of the powder layer formed by the powder for stacking modeling is good. If the D90 of the powder for stacking modeling is 40.0 μm or less, the uniformity of the powder layer formed by the powder for stacking modeling is good.

[0081] The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the powder for stacking modeling is 15.0 volume % or more, preferably 15.5 volume % or more, and more preferably 16.0 volume % or more. The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the powder for stacking modeling is 22.0 volume % or less, preferably 21.0 volume % or less, and more preferably 20.0 volume % or less. The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the powder for stacking modeling is 15.0 to 22.0 volume %, preferably 15.5 to 21.0 volume %, and more preferably 16.0 to 20.0 volume %. If the volume ratio of particles with a particle size of 16.8 to 60.0 μm is within the above range, moderate fluidity of the powder for stacking modeling can be expected. The volume ratio of particles having a particle size of 16.8 to 60.0 μm in the laminated modeling powder is a value determined by measuring with an electrical resistance particle size distribution measuring apparatus (Beckman Coulter, Multisizer 4) at an aperture size of 100 μm.

[0082] The volume ratio of particles with a particle size of 2.0 μm or more in the powder for stacking modeling is preferably 90.0 to 100 volume %, more preferably 93.0 to 100 volume %, and further preferably 95.0 to 100 volume %. If the volume ratio of particles with a particle size of 2.0 μm or more is 90.0 volume % or more, the shrinkage rate during sintering can be reduced. The volume ratio of particles with a particle size of 2.0 μm or more in the powder for stacking modeling is a value determined using a laser diffraction-scattering particle size distribution measuring device (Michiko Baier Co., Ltd., MT3300EXII).

[0083] The ratio of D50 to D10 (D50 / D10) of the powder for laminated modeling is preferably 2.0 to 2.2. If D50 / D10 is within the above range, the powder for laminated modeling can be expected to have both good laying properties that can form a uniform powder layer and moderate fluidity that can maintain shape stability during the period from the application of the binder to the sintering process.

[0084] The ratio of D90 to D10 (D90 / D10) of the powder for stacked modeling is preferably 6.0 or more, more preferably 6.2 or more, and further preferably 6.5 or more. The ratio of D90 to D10 (D90 / D10) of the powder for stacked modeling is preferably 8.0 or less, more preferably 7.5 or less, and further preferably 7.0 or less. The ratio of D90 to D10 (D90 / D10) of the powder for stacked modeling is preferably 6.0 to 8.0, more preferably 6.2 to 7.5, and further preferably 6.5 to 7.0. If D90 / D10 is 8.0 or less, the particle size distribution of the powder is within a certain range, so fine particles are appropriately arranged around the coarse particles, which can make the fluidity appropriate. If D90 / D10 is 6.0 or more, fine particles are appropriately arranged between the coarse particles, which can make the volume density appropriate.

[0085] The ratio of D90 to D50 (D90 / D50) of the powder for stacking modeling is preferably 2.8 to 3.6, more preferably 2.9 to 3.5, and further preferably 3.2 to 3.4. If D90 / D50 is 3.6 or less, the particle size distribution of the powder is within a certain range, so that fine particles are appropriately arranged around the coarse particles, and the flowability can be appropriate. If D90 / D50 is 2.8 or more, fine particles are appropriately arranged between the coarse particles, and the bulk density can be appropriate.

[0086] The angle of repose of the layered modeling powder is preferably 55 to 58 degrees, more preferably 56 to 57 degrees. The angle of repose is one of the indicators of the fluidity of the powder. If the angle of repose of the layered modeling powder is 55 degrees or more, the shape stability of the powder layer formed by the layered modeling powder is good. If the angle of repose of the layered modeling powder is 58 degrees or less, the layered modeling powder can be smoothly supplied to the modeling table and evenly spread.

[0087] The BET specific surface area of ​​the powder for laminated molding is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 The BET specific surface area of ​​the powder for laminated molding is preferably 10.0 m 2 / g or less, more preferably 5.0m 2 / g or less, more preferably 2.0m 2 The BET specific surface area of ​​the powder for laminated molding is preferably 0.1 to 10.0 m 2 / g, more preferably 0.1 to 5.0 m 2 / g, more preferably 0.2 to 2.0 m 2 / g. If the BET specific surface area is 0.1m 2 / g or more, the shape stability of the powder layer formed by the laminated molding powder is good. 2 / g or less, the layered modeling powder can be smoothly supplied to the modeling table and evenly spread.

[0088] The shape of the powder for stacking modeling is not particularly limited. For example, spherical, ellipsoidal, scaly, amorphous, etc. can be cited. Among them, in order to easily obtain an appropriate volume density, a spherical shape is preferred. From this viewpoint, the roundness of the powder for stacking modeling is preferably 0.80 or more, more preferably 0.90 or more, and further preferably 0.95 or more. The upper limit of the roundness of the powder for stacking modeling is not particularly limited, but can be set to 1.00 or 0.99, for example. If the roundness is 0.80 or more, the compacting volume density can be increased.

[0089] The powder for stacking modeling is preferably at least one selected from silicon dioxide, aluminum oxide, zirconium oxide and titanium dioxide, more preferably aluminum oxide, and further preferably spherical aluminum oxide. Aluminum oxide has high thermal conductivity, melting point and hardness, is cheap, and is strong in acid and alkali resistance, so it is preferred from this point of view. The volume proportion of aluminum oxide in the powder for stacking modeling is preferably 50 volume % or more, more preferably 60 volume % or more, and further preferably 80 volume % or more. The upper limit of the volume proportion of aluminum oxide in the powder for stacking modeling is not particularly limited, for example, it can be set to 100 volume %, 98 volume % or 95 volume %.

[0090] When the powder for laminated molding is alumina, the compacting bulk density of the powder for laminated molding at a pressure of 98 MPa is preferably 2.52 to 2.54 g / cm 3 If the powder for laminate molding is pressed at a pressure of 98 MPa, the bulk density is 2.52 g / cm 3 If the compacting bulk density of the powder for laminated molding at a pressure of 98 MPa is 2.54 g / cm 3 Next, when the binder is applied, the binder can easily enter between the powder materials, and the strength of the molded body and the sintered body can be sufficient.

[0091] The powder for layered modeling has good laying properties and shape stability of the powder layer, as well as an appropriate bulk density, and is therefore very suitable for use in the binder jetting method. The powder for layered modeling can also be used in the powder bed fusion method, in which a powder bed covered with powder material is irradiated with a laser or electron beam to selectively melt it for modeling, and other powder layered modeling methods.

[0092] The powder for lamination molding can also be used for other purposes besides lamination molding. For example, the powder for lamination molding can be used as a filler in coatings such as heat dissipation coatings, heat insulation coatings, and wear-resistant coatings, a filler in thermally conductive resin compositions having bonding properties, and a filler in thermally conductive coating materials having the function of curing in the atmosphere.

[0093] The inorganic oxide powder according to one embodiment is an alumina powder having D10 of 1.0 to 4.0 μm, D50 of 5.5 to 9.0 μm, D90 of 20.0 to 40.0 μm, and a volume ratio of particles having a particle size of 16.8 to 60.0 μm of 15.0 to 22.0 vol%.

[0094] <Method for producing powder for laminated modeling>

[0095] The powder for laminated modeling can be produced, for example, by mixing a plurality of inorganic oxide powders having different particle size distributions so that the particle size distribution of the powder for laminated modeling is within a specified range. The particle size distribution of the powder for laminated modeling can also be adjusted by screening, etc. The particle size distribution of the powder for laminated modeling can be adjusted to an appropriate range by selecting the type (particle size distribution) and the amount of the inorganic oxide powder to be mixed. The mixing method of the materials is not particularly limited, and for example, a method of dry mixing or wet mixing of the materials can be cited. Mixing can be performed manually or using a blender.

[0096] As a more specific method for producing the powder for laminated modeling, for example, there is a method of mixing the coarse inorganic oxide powder (A) shown below and the fine inorganic oxide powder (B) having a D50 smaller than that of the coarse inorganic oxide powder (A).

[0097] [Coarse-grained inorganic oxide powder (A)]

[0098] The D50 of the coarse-grained inorganic oxide powder (A) used is preferably 9.0 to 25.0 μm, more preferably 12.0 to 20.0 μm, and further preferably 14.0 to 18.0 μm. The D10 of the coarse-grained inorganic oxide powder (A) is preferably 1.0 to 8.0 μm, more preferably 2.0 to 7.5 μm, and further preferably 3.0 to 7.0 μm. The D90 of the coarse-grained inorganic oxide powder (A) is preferably 28.0 to 40.0 μm, more preferably 28.5 to 38.0 μm, and further preferably 29.0 to 36.0 μm.

[0099] The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 1.5 to 3.5, more preferably 1.7 to 3.2, and even more preferably 2.0 to 3.0. The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 3.5 to 9.0, more preferably 4.0 to 7.0, and even more preferably 4.5 to 6.0. The ratio of D90 to D50 (D90 / D50) of the coarse-grained inorganic oxide powder (A) is preferably 1.7 to 2.3, more preferably 1.8 to 2.2, and even more preferably 1.9 to 2.0.

[0100] The shape of the coarse-grained inorganic oxide powder (A) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, a spherical shape is preferred in order to easily obtain an appropriate bulk density.

[0101] The coarse-grained inorganic oxide powder (A) is preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the coarse-grained inorganic oxide powder (A) is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 80% by volume or more. The upper limit of the volume ratio of alumina in the coarse-grained inorganic oxide powder (A) is not particularly limited, and for example, can be set to 100% by volume, 98% by volume or 95% by volume.

[0102] [Fine-particle inorganic oxide powder (B)]

[0103] The D50 of the fine-particle inorganic oxide powder (B) is smaller than the D50 of the coarse-particle inorganic oxide powder (A). The D50 of the fine-particle inorganic oxide powder (B) used is preferably 5.0 to 8.0 μm, more preferably 5.5 to 7.8 μm, and further preferably 6.0 to 7.5 μm. The D10 of the fine-particle inorganic oxide powder (B) is preferably 1.0 to 4.0 μm, more preferably 2.0 to 3.8 μm, and further preferably 2.5 to 3.5 μm. The D90 of the fine-particle inorganic oxide powder (B) is preferably 9.0 to 25.0 μm, more preferably 12.0 to 24.0 μm, and further preferably 14.0 to 23.0 μm.

[0104] The ratio of D50 to D10 (D50 / D10) of the fine-particle inorganic oxide powder (B) is preferably 1.5 to 5.0, more preferably 1.7 to 4.0, and even more preferably 1.8 to 3.0. The ratio of D90 to D10 (D90 / D10) of the fine-particle inorganic oxide powder (B) is preferably 3.5 to 9.0, more preferably 4.5 to 8.0, and even more preferably 5.5 to 7.0. The ratio of D90 to D50 (D90 / D50) of the fine-particle inorganic oxide powder (B) is preferably 2.5 to 3.5, more preferably 2.8 to 3.2, and even more preferably 2.7 to 2.9.

[0105] The shape of the fine-particle inorganic oxide powder (B) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, a spherical shape is preferred in order to easily obtain an appropriate bulk density.

[0106] The fine-particle inorganic oxide powder (B) is preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the fine-particle inorganic oxide powder (B) is preferably 50 volume % or more, more preferably 60 volume % or more, and further preferably 80 volume % or more. The upper limit of the volume ratio of alumina in the fine-particle inorganic oxide powder (B) is not particularly limited, and for example, it can be set to 100 volume %, 98 volume % or 95 volume %.

[0107] The volume ratio of the coarse inorganic oxide powder (A) relative to the total volume of the coarse inorganic oxide powder (A) and the fine inorganic oxide powder (B) is selected so that the particle size distribution of the powder for stacking molding is within an appropriate range, for example, can be set to 9.5 to 29.0 volume %.

[0108] <Layering modeling powder>

[0109] In the powder layering molding method in which a roller or the like is used to spread the powder material, the compacting volume density of the material is important. Inorganic oxide powders with a smaller D50 tend to have lower volume density and lower fluidity than inorganic oxide powders with a larger D50. The inventors have found that by combining a small amount of coarse inorganic oxide powder (A) with a fine inorganic oxide powder (B) having a smaller D50 than the coarse inorganic oxide powder (A), a good balance between the fluidity and volume density of the powder material can be achieved. This is completely different from the design concept of the previous powder material in which fine particles are filled into the gaps between the coarse particles to increase the volume density.

[0110] The powder for laminated molding is preferably a coarse-grained inorganic oxide powder (A) having a D50 (D A 50) and D50 (D B50) Satisfy D A 50-D B 50 ≥ 3.5 μm. Within this range, the advantages of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) are both effective, and a powder having a good balance between fluidity and bulk density can be obtained. From the same viewpoint, D is more preferred. A 50-D B 50≥5.5μm, further preferred D A 50-D B 50≥7.5μm.D A 50-D B The upper limit of 50 may be set to 12.0 μm, 15.0 μm, or 19.0 μm.

[0111] In the first embodiment, the powder for stacked modeling includes a coarse-grained inorganic oxide powder (A) having a D50 of 9.0 to 25.0 μm and a fine-grained inorganic oxide powder (B) having a D50 smaller than that of the coarse-grained inorganic oxide powder (A), and the volume ratio of the coarse-grained inorganic oxide powder (A) is 9.5 to 29.0 volume % relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B).

[0112] In this embodiment, the volume ratio of the coarse-grained inorganic oxide powder (A) is 9.5 to 29.0 volume %, preferably 10.5 to 20.0 volume %, and more preferably 11.6 to 15.0 volume % relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). The volume ratio of the coarse-grained inorganic oxide powder (A) is 9.5 volume % or more, preferably 10.5 volume % or more, and more preferably 11.6 volume % or more relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). The volume ratio of the coarse-grained inorganic oxide powder (A) is 29.0 volume % or less, preferably 20.0 volume % or less, and more preferably 15.0 volume % or less relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). If the above-mentioned volume ratio is 9.5 volume % or more, the bulk density can be increased to be within a suitable range as a powder for stacking molding. When the volume ratio is 29.0 volume % or less, the fluidity can be suppressed to be within a suitable range as a powder for laminated modeling.

[0113] In this embodiment, the particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is preferably 0.26 to 1.15, more preferably 0.27 to 0.74, and further preferably 0.29 to 0.32. The particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is preferably 0.26 or more, more preferably 0.27 or more, and further preferably 0.29 or more. The particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is preferably 1.15 or less, more preferably 0.74 or less, and further preferably 0.32 or less. If the above-mentioned particle size volume ratio is 0.26 or more, the bulk density can be increased to be within a range suitable for powder for stacking modeling. If the particle size volume ratio is 1.15 or less, the fluidity can be suppressed to be within a range suitable for powder for stacking modeling.

[0114] In the second embodiment, the powder for stacked modeling includes a coarse-grained inorganic oxide powder (A) having a D50 of 9.0 to 25.0 μm and a fine-grained inorganic oxide powder (B) having a D50 smaller than that of the coarse-grained inorganic oxide powder (A), and the particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 0.26 to 1.15.

[0115] In this embodiment, the particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 0.26 to 1.15, preferably 0.27 to 0.74, and more preferably 0.29 to 0.32. The particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 0.26 or more, preferably 0.27 or more, and more preferably 0.29 or more. The particle size volume ratio of the coarse-grained inorganic oxide powder (A) to the fine-grained inorganic oxide powder (B) is 1.15 or less, preferably 0.74 or less, and more preferably 0.32 or less. If the above-mentioned particle size volume ratio is 0.26 or more, the bulk density can be increased to be within a range suitable for powder for stacking modeling. If the particle size volume ratio is 1.15 or less, the fluidity can be suppressed to be within a range suitable for powder for stacking modeling.

[0116] In this embodiment, the volume ratio of the coarse-grained inorganic oxide powder (A) is preferably 9.5 to 29.0 volume %, more preferably 10.5 to 20.0 volume %, and more preferably 12.0 to 15.0 volume % relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). The volume ratio of the coarse-grained inorganic oxide powder (A) is preferably 9.5 volume % or more, more preferably 10.5 volume % or more, and further preferably 12.0 volume % or more relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). The volume ratio of the coarse-grained inorganic oxide powder (A) is preferably 29.0 volume % or less, more preferably 20.0 volume % or less, and further preferably 15.0 volume % or less relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B). If the above-mentioned volume ratio is 9.5 volume % or more, the bulk density can be increased to be within a suitable range as a powder for stacking molding. When the volume ratio is 29.0 volume % or less, the fluidity can be suppressed to be within a suitable range as a powder for laminated modeling.

[0117] The D50 of the powder for laminated modeling is preferably 5.5 to 9.0 μm, more preferably 6.0 to 8.5 μm, and further preferably 6.5 to 8.0 μm. If the D50 of the powder for laminated modeling is 5.5 μm or more, the shape stability of the powder layer formed by the powder for laminated modeling is better, and the shrinkage rate during sintering can be reduced. If the D50 of the powder for laminated modeling is 9.0 μm or less, the bulk density and fluidity can be within an appropriate range.

[0118] The D10 of the powder for laminated modeling is preferably 1.0 to 4.0 μm, more preferably 2.0 to 3.8 μm, and further preferably 3.0 to 3.6 μm. If the D10 of the powder for laminated modeling is 1.0 μm or more, the shrinkage rate during sintering can be reduced. If the D10 of the powder for laminated modeling is 4.0 μm or less, the bulk density and fluidity can be within an appropriate range.

[0119] The D90 of the laminated modeling powder is preferably 20.0 to 40.0 μm, more preferably 20.5 to 30.0 μm, and further preferably 21.0 to 25.0 μm. If the D90 of the laminated modeling powder is 20.0 μm or more, the shape stability of the powder layer formed by the laminated modeling powder is better. If the D90 of the laminated modeling powder is 40.0 μm or less, the uniformity of the powder layer formed by the laminated modeling powder is better.

[0120] The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the powder for stacking modeling is preferably 15.0 to 26.0 volume %, more preferably 15.0 to 22.0 volume %, and further preferably 16.0 to 20.0 volume %. If the volume ratio of particles with a particle size of 16.8 to 60.0 μm is within the above range, moderate fluidity of the powder material can be expected. The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the powder for stacking modeling is a value determined by measuring the pore size to 100 μm using a resistance method particle size distribution measuring device (Beckman Coulter, Multisizer 4).

[0121] The volume ratio of particles with a particle size of 2.0 μm or more in the powder for stacking modeling is preferably 90.0 to 100 volume %, more preferably 93.0 to 100 volume %, and further preferably 95.0 to 100 volume %. If the volume ratio of particles with a particle size of 2.0 μm or more is 90.0 volume % or more, the shrinkage rate during sintering can be reduced. The volume ratio of particles with a particle size of 2.0 μm or more in the powder for stacking modeling is a value determined using a laser diffraction-scattering particle size distribution measuring device (Michiko Baier Co., Ltd., MT3300EXII).

[0122] The ratio of D50 to D10 (D50 / D10) of the powder for laminated modeling is preferably 2.0 to 2.2. If D50 / D10 is within the above range, the powder for laminated modeling can be expected to have both good laying properties that can form a uniform powder layer and moderate fluidity that can maintain shape stability during the period from the application of the binder to the sintering process.

[0123] The ratio of D90 to D10 (D90 / D10) of the powder for stacking modeling is preferably 6.0 to 8.0, more preferably 6.2 to 7.5, and further preferably 6.5 to 7.0. If D90 / D10 is 8.0 or less, the particle size distribution of the powder is within a certain range, so that fine particles are appropriately arranged around the coarse particles, and the flowability can be appropriate. If D90 / D10 is 6.0 or more, fine particles are appropriately arranged between the coarse particles, and the bulk density can be appropriate.

[0124] The ratio of D90 to D50 (D90 / D50) of the powder for laminated modeling is preferably 2.8 to 3.6, more preferably 2.9 to 3.5, and further preferably 3.2 to 3.4. If D90 / D50 is 3.6 or less, the particle size distribution of the powder is within a certain range, and fine particles are appropriately arranged around the coarse particles, which can make the fluidity appropriate. If D90 / D50 is 2.8 or more, fine particles are appropriately arranged between the coarse particles, which can make the bulk density appropriate.

[0125] The angle of repose of the powder for stacking modeling is preferably 55 to 58 degrees, and more preferably 56 to 57 degrees. The angle of repose is one of the indicators indicating the fluidity of the powder. If the angle of repose of the powder for stacking modeling is 55 degrees or more, the shape stability of the powder layer formed by the powder for stacking modeling is good. If the angle of repose of the powder for stacking modeling is 58 degrees or less, the powder for stacking modeling can be smoothly supplied to the molding table and evenly spread.

[0126] The BET specific surface area of ​​the powder for laminated molding is preferably 0.1 to 10.0 m 2 / g, more preferably 0.1 to 5.0 m 2 / g, more preferably 0.2 to 2.0 m 2 / g. If the BET specific surface area is 0.1m 2 / g or more, the shape stability of the powder layer formed by the laminated molding powder is good. 2 / g or less, the layered modeling powder can be smoothly supplied to the modeling table and evenly spread.

[0127] The shape of the powder for stacking modeling is not particularly limited. For example, spherical, ellipsoidal, scaly, amorphous, etc. can be cited. Among them, in order to easily obtain an appropriate volume density, a spherical shape is preferred. From this viewpoint, the roundness of the powder for stacking modeling is preferably 0.80 or more, more preferably 0.90 or more, and further preferably 0.95 or more. The upper limit of the roundness of the powder for stacking modeling is not particularly limited, but can be set to 1.00 or 0.99, for example. If the roundness is 0.80 or more, the compacting volume density can be increased.

[0128] The powder for stacking modeling is preferably at least one selected from silicon dioxide, aluminum oxide, zirconium oxide and titanium dioxide, more preferably aluminum oxide, and further preferably spherical aluminum oxide. Aluminum oxide has high thermal conductivity, melting point and hardness, is cheap, and is strong in acid and alkali resistance, so it is preferred from this point of view. The volume proportion of aluminum oxide in the powder for stacking modeling is preferably 50 volume % or more, more preferably 60 volume % or more, and further preferably 80 volume % or more. The upper limit of the volume proportion of aluminum oxide in the powder for stacking modeling is not particularly limited, for example, it can be set to 100 volume %, 98 volume % or 95 volume %.

[0129] When the powder for laminated molding is alumina, the compacting bulk density of the powder for laminated molding at a pressure of 98 MPa is preferably 2.52 to 2.54 g / cm 3 If the powder for laminate molding is pressed at a pressure of 98 MPa, the bulk density is 2.52 g / cm 3If the compacting bulk density of the powder for laminated molding at a pressure of 98 MPa is 2.54 g / cm 3 Next, when the binder is applied, the binder can easily enter between the powder materials, and the strength of the molded body and the sintered body can be sufficient.

[0130] The powder for layered modeling has good laying properties, shape stability of the powder layer, and appropriate bulk density, so it is very suitable for use in the binder jetting method. The powder for layered modeling can also be used in the powder bed fusion method, which selectively melts a powder bed covered with powder materials by irradiating it with a laser or electron beam, and other powder layered modeling methods.

[0131] The powder for lamination molding can also be used for other purposes besides lamination molding. For example, the powder for lamination molding can be used as a filler in coatings such as heat dissipation coatings, heat insulation coatings, and wear-resistant coatings, a filler in thermally conductive resin compositions having bonding properties, and a filler in thermally conductive coating materials having the function of curing in the atmosphere.

[0132] [Coarse-grained inorganic oxide powder (A)]

[0133] The D50 of the coarse-grained inorganic oxide powder (A) is 9.0 μm or more, preferably 12.0 μm or more, and more preferably 14.0 μm or more. The D50 of the coarse-grained inorganic oxide powder (A) is 25.0 μm or less, preferably 20.0 μm or less, and more preferably 18.0 μm or less. The D50 of the coarse-grained inorganic oxide powder (A) is 9.0 to 25.0 μm, preferably 12.0 to 20.0 μm, and more preferably 14.0 to 18.0 μm. If the D50 of the coarse-grained inorganic oxide powder (A) is 9.0 μm or more, it is easy to fill the powder for stacking modeling at a high density. If the D50 of the coarse-grained inorganic oxide powder (A) is 25.0 μm or less, the angle of repose of the powder for stacking modeling can be controlled within an appropriate range.

[0134] The D10 of the coarse-grained inorganic oxide powder (A) is preferably 1.0 to 8.0 μm, more preferably 2.0 to 7.5 μm, and further preferably 3.0 to 7.0 μm. If the D10 of the coarse-grained inorganic oxide powder (A) is 1.0 μm or more, the shrinkage during sintering can be reduced. If the D10 of the coarse-grained inorganic oxide powder (A) is 8.0 μm or less, appropriate fluidity of the powder material can be expected.

[0135] The D90 of the coarse-grained inorganic oxide powder (A) is preferably 28.0 to 40.0 μm, more preferably 28.5 to 38.0 μm, and further preferably 29.0 to 36.0 μm. If the D90 of the coarse-grained inorganic oxide powder (A) is 28.0 μm or more, the density of the molded body formed by the laminated molding powder can be increased, and the shape stability is better. If the D90 of the coarse-grained inorganic oxide powder (A) is 40.0 μm or less, the uniformity of the powder layer formed by the laminated molding powder is better.

[0136] The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 1.5 or more, more preferably 1.7 or more, and further preferably 2.0 or more. The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 3.5 or less, more preferably 3.2 or less, and further preferably 3.0 or less. The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 1.5 to 3.5, more preferably 1.7 to 3.2, and further preferably 2.0 to 3.0. If D50 / D10 is within the above range, an increase in the volume density of the press-molded product can be expected.

[0137] The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 4.0 or more, more preferably 4.5 or more, and further preferably 5.0 or more. The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 7.0 or less, more preferably 6.0 or less, and further preferably 5.5 or less. The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide powder (A) is preferably 4.0 to 7.0, more preferably 4.5 to 6.0, and further preferably 5.0 to 5.5. If D90 / D10 is within the above range, the particle size distribution is within a certain range, so it is easy to use as a base material for laminated modeling powder, and can improve the bulk density and fluidity in a well-balanced manner.

[0138] The ratio of D90 to D50 (D90 / D50) of the coarse inorganic oxide powder (A) is preferably 1.7 to 2.3, more preferably 1.8 to 2.2, and even more preferably 1.9 to 2.0. When D90 / D50 is within the above range, the flowability of the powder for laminated molding can be within an appropriate range.

[0139] The shape of the coarse-grained inorganic oxide powder (A) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, a spherical shape is preferred in order to easily obtain an appropriate bulk density.

[0140] The coarse-grained inorganic oxide powder (A) is preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the coarse-grained inorganic oxide powder (A) is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 80% by volume or more. The upper limit of the volume ratio of alumina in the coarse-grained inorganic oxide powder (A) is not particularly limited, and for example, can be set to 100% by volume, 98% by volume or 95% by volume.

[0141] [Fine-particle inorganic oxide powder (B)]

[0142] The D50 of the fine-particle inorganic oxide powder (B) is smaller than the D50 of the coarse-particle inorganic oxide powder (A). The D50 of the fine-particle inorganic oxide powder (B) is preferably 5.0 μm or more, more preferably 5.5 μm or more, and further preferably 6.0 μm or more. The D50 of the fine-particle inorganic oxide powder (B) is preferably 8.0 μm or less, more preferably 7.8 μm or less, and further preferably 7.5 μm or less. The D50 of the fine-particle inorganic oxide powder (B) is preferably 5.0 to 8.0 μm, more preferably 5.5 to 7.8 μm, and further preferably 6.0 to 7.5 μm. If the D50 of the fine-particle inorganic oxide powder (B) is 5.0 μm or more, it is easy to fill the powder for stacking modeling at a high density. If the D50 of the fine-particle inorganic oxide powder (B) is 8.0 μm or less, the angle of repose of the stacking modeling powder can be increased and the fluidity can be suppressed.

[0143] The D10 of the fine-particle inorganic oxide powder (B) is preferably 1.0 to 4.0 μm, more preferably 2.0 to 3.8 μm, and further preferably 2.5 to 3.5 μm. If the D10 of the fine-particle inorganic oxide powder (B) is within the above range, it can be expected that the fine-particle inorganic oxide powder (B) acts as a bearing (bearing effect) and the fluidity is within an appropriate range.

[0144] The D90 of the fine-particle inorganic oxide powder (B) is preferably 9.0 to 25.0 μm, more preferably 12.0 to 24.0 μm, and even more preferably 14.0 to 23.0 μm. When the D90 of the fine-particle inorganic oxide powder (B) is within the above range, appropriate flowability of the powder for laminated molding can be expected.

[0145] The ratio of D50 to D10 (D50 / D10) of the fine-particle inorganic oxide powder (B) is preferably 1.5 to 5.0, more preferably 1.7 to 4.0, and even more preferably 1.8 to 3.0. If D50 / D10 is within the above range, the effect of suppressing the aggregation of the fine-particle inorganic oxide powder (B) can be expected, and the bulk density of the powder for laminated molding can be increased.

[0146] The ratio of D90 to D10 (D90 / D10) of the fine-particle inorganic oxide powder (B) is preferably 3.5 to 9.0, more preferably 4.5 to 8.0, and further preferably 5.5 to 7.0. If D90 / D10 is within the above range, the particle size distribution is within a certain range, so it is easy to use as a base material for laminated molding powder, and the bulk density and fluidity can be improved in a good balance.

[0147] The ratio of D90 to D50 (D90 / D50) of the fine-particle inorganic oxide powder (B) is preferably 2.5 to 3.5, more preferably 2.8 to 3.2, and even more preferably 2.7 to 2.9. When D90 / D50 is within the above range, the flowability of the powder for laminated molding can be within an appropriate range.

[0148] The shape of the fine-particle inorganic oxide powder (B) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, a spherical shape is preferred in order to easily obtain an appropriate bulk density.

[0149] The fine-particle inorganic oxide powder (B) is preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the fine-particle inorganic oxide powder (B) is preferably 50 volume % or more, more preferably 60 volume % or more, and further preferably 80 volume % or more. The upper limit of the volume ratio of alumina in the fine-particle inorganic oxide powder (B) is not particularly limited, and for example, it can be set to 100 volume %, 98 volume % or 95 volume %.

[0150] <Method for producing powder for laminated modeling>

[0151] The powder for laminated modeling can be produced by mixing a coarse-grained inorganic oxide powder (A) and a fine-grained inorganic oxide powder (B). The mixing method of the materials is not particularly limited, and for example, a method of dry mixing or wet mixing of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) can be cited. Mixing can be performed manually or using a mixer.

[0152] <Method for producing a three-dimensional laminated structure>

[0153] The three-dimensional layered molding body can be produced by processing layered molding powder using a known powder layered molding method. Examples of the powder layered molding method include a binder jet method and a powder bed fusion method. The powder layered molding method generally includes the following steps.

[0154] (1) a step of supplying powder for lamination molding to a molding table of a powder lamination molding device;

[0155] (2) a step of spreading the supplied laminated modeling powder uniformly and thinly using a roller or the like to form a thin layer of the laminated modeling powder;

[0156] (3) a step of irradiating the formed thin layer of the layered modeling powder with a laser or electron beam, or applying a liquid containing an adhesive to bond the layered modeling powder;

[0157] (4) A step of supplying new layered modeling powder onto the solidified layered modeling powder.

[0158] Thereafter, by repeating steps (2) to (4), a target three-dimensional stacked structure can be manufactured.

[0159] As a method for applying a liquid containing an adhesive, a method for discharging a liquid containing an adhesive is preferred. There are no particular restrictions on the method for discharging a liquid containing an adhesive, and examples thereof include a dispenser method, a spray method, and an inkjet method. Among them, the inkjet method is preferred because the quantitative properties of the droplets are good and a large area can be coated.

[0160] When using the inkjet method, the liquid containing the adhesive can be applied using an inkjet head having a nozzle for discharging the liquid. As the inkjet head, an inkjet head in a known inkjet printer can be used very suitably, for example, the industrial inkjet RICOH MH / GH series (Ricoh Co., Ltd.) can be cited.

[0161] The binder is not particularly limited, and known binders such as polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, acrylic resin, and polyamide can be used. The viscosity of the binder can be adjusted using an appropriate solvent.

[0162] <Method for producing sintered body>

[0163] The sintered body can be produced by sintering the three-dimensional stacked body using a known sintering method. It is preferred that a degreasing treatment be performed before the sintering treatment. A specific method for producing the sintered body is exemplified below.

[0164] The three-dimensional stacked body is placed in a sintering furnace, and the temperature in the furnace is raised to the degreasing treatment temperature. The degreasing treatment temperature can be appropriately set in the range of 500 to 700°C, for example. Thereafter, the temperature in the furnace is maintained at the degreasing treatment temperature for 0.5 to 4 hours to burn the organic components (degreasing treatment). The degreasing time can be set according to the type of binder and the ratio of organic components in the three-dimensional stacked body. Next, the temperature in the furnace is raised to the sintering treatment temperature. The sintering treatment temperature can be appropriately set in the range of 900 to 1300°C, for example. Thereafter, the temperature in the furnace is maintained at the sintering treatment temperature for 1 to 7 hours to sinter the three-dimensional stacked body, thereby obtaining a sintered body (sintering treatment). The sintering temperature and sintering time can be set according to the type of inorganic oxide powder.

[0165] Example

[0166] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0167] <Materials used>

[0168] Coarse-grained inorganic oxide powder (A): spherical alumina (Alnabis (trademark) / CB manufactured by Showa Denko K.K.): true density 3.95 g / m 3

[0169] Fine-particle inorganic oxide powder (B): spherical alumina (Alnabis (trademark) / CB manufactured by Showa Denko K.K.): true density 3.95 g / m 3

[0170] <Evaluation method>

[0171] (Volume Density)

[0172] The bulk density is evaluated by using the compression molding bulk density under a pressure of 98 MPa. Specifically, a sample is placed in a circular mold frame (inner diameter 30 mm), and a molded body is produced under a pressure of 98 MPa using a commercially available press. The density of the resulting molded body is determined as the compression molding bulk density under a pressure of 98 MPa. If the compression molding bulk density is 2.52 g / cm 3 If the compacting volume density is 2.54 g / cm 3 Below, when the binder is applied, the binder can enter between the powder materials, which is excellent. That is, the bulk density of the pressed molded product is 2.52 to 2.54 g / cm 3 In the case of , the bulk density was evaluated to be good.

[0173] (Roundness)

[0174] The area S and the perimeter L were measured using FPIA-3000 manufactured by Malvern Panalytical. As a pre-treatment, due to the measurement range of the device, about 10 g of the sample was placed in a metal sieve with a diameter of 200 mm (mesh size 25 μm), and particles larger than 25 μm were removed with spray water. The sample under the sieve was transferred to a plastic container as a measurement sample. The measurement conditions were set to LPF / HPF standard (20x lens) and bright field, and particle sheath reagent (particle sheath) manufactured by Malvern Panalytical was used as the measurement solvent. 2 g of the measurement sample was weighed into a 50 mL beaker in such a way that the effective number of analysis became 5000, and pure water was used to put it into the device for measurement. As data processing after the measurement, the data when there were multiple particles on one screen was deleted, and the average roundness was calculated.

[0175] (Liquidity)

[0176] The fluidity is evaluated by the angle of repose. If the angle of repose is 55° or more, the shape stability (fluidity) that can maintain the shape from the application of the binder to the sintering process is excellent. If it is 58° or less, the laying property (fluidity) that can be smoothly supplied to the molding table and evenly spread is excellent. That is, when the angle of repose is 55 to 58°, the fluidity is evaluated to be good.

[0177] [Example 1]

[0178] The coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) having the particle size and particle size ratio described in Table 1 were mixed using a swing mixer so that the volume ratio of the coarse-grained inorganic oxide powder (A) relative to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) was 11.1 volume %, thereby obtaining a powder for laminated molding. The particle size distribution, BET specific surface area, roundness, fluidity (angle of repose) and compacting bulk density of the obtained powder for laminated molding were evaluated. The results are shown in Table 2.

[0179] [Examples 2 to 6, Comparative Examples 1 to 16]

[0180] The powder for laminated molding was obtained in the same manner as in Example 1 except that the volume ratio of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) and the coarse-grained inorganic oxide powder (A) to the total volume of the coarse-grained inorganic oxide powder (A) and the fine-grained inorganic oxide powder (B) was set as shown in Table 1. The particle size distribution, BET specific surface area, roundness, fluidity (angle of repose) and compacting bulk density of the obtained powder for laminated molding were evaluated. The results are shown in Table 2. In addition, "-" is recorded if no evaluation is made.

[0181]

[0182]

[0183]

[0184]

[0185] In Examples 1 to 6, since the angle of repose is in the range of 55 to 58 degrees and has moderate fluidity, it is considered that when used in the binder jetting method, a uniform powder layer can be formed when a thin layer of the laminated modeling powder is formed, and the shape can be maintained during the period from the application of the binder to the sintering process. In addition, in Examples 1 to 6, since the compacting bulk density is in the range of 2.52 to 2.54 g / cm 3 The range has an appropriate compacting bulk density, so it is considered that when used in the binder jetting method, the binder can enter between the powder materials and a low shrinkage rate during sintering can be achieved.

[0186] Industrial Applicability

[0187] By using the powder for stacking modeling of one embodiment, in the stacking modeling method (binder spraying method) of spraying liquid binder onto the spread powder material and solidifying it, a modeling body with few voids can be produced, and the effect of reducing the heating shrinkage of the modeling body during the sintering process can be expected.

Claims

1. A powder for stacking modeling, which is an inorganic oxide powder, D10 is 1.0~4.0μm, D50 is 5.5~9.0μm, D90 is 20.0~40.0μm, The volume ratio of particles having a particle size of 16.8 to 60.0 μm is 15.0 to 22.0% by volume. 2 . The powder for laminated modeling according to claim 1 , wherein the volume ratio of particles having a particle size of 2.0 μm or more is 90.0 to 100 volume %.

3. The powder for laminated molding according to claim 1, The ratio of D50 to D10, i.e. D50 / D10, is 2.0 to 2.

2. The ratio of D90 to D10, i.e. D90 / D10, is 6.0 to 8.

0.

4. The powder for laminated molding according to any one of claims 1 to 3, wherein the BET specific surface area is 0.1 to 10.0 m 2 / g.

5. The powder for laminated modeling according to any one of claims 1 to 3, which is spherical in shape. 6 . The powder for laminated modeling according to claim 1 , which is aluminum oxide.

7. The powder for laminated molding according to claim 6, wherein the bulk density of the powder after compaction at a pressure of 98 MPa is 2.52 to 2.54 g / cm 3 .

8. A powder for layered modeling, comprising: Coarse-grained inorganic oxide powder A having a D50 of 9.0 to 25.0 μm; and D50 is smaller than the coarse inorganic oxide powder A, and the fine inorganic oxide powder B The volume ratio of the coarse-grained inorganic oxide powder A to the total volume of the coarse-grained inorganic oxide powder A and the fine-grained inorganic oxide powder B is 9.5 to 29.0 volume %. 9 . The powder for laminated molding according to claim 8 , wherein a particle size volume ratio of the coarse-grained inorganic oxide powder A to the fine-grained inorganic oxide powder B is 0.26 to 1.

15.

10. The powder for laminated molding according to claim 8 or 9, wherein the D50 (D A 50 and D50 of the microparticle inorganic oxide powder B, i.e. D B 50 Satisfaction D A 50-D B 50≥3.5μm.

11. A powder for layered modeling, comprising: Coarse-grained inorganic oxide powder A having a D50 of 9.0 to 25.0 μm; and D50 is smaller than the coarse inorganic oxide powder A, and the fine inorganic oxide powder B The particle size volume ratio of the coarse-grained inorganic oxide powder A to the fine-grained inorganic oxide powder B is 0.26 to 1.

15. 12 . The powder for laminated molding according to claim 11 , wherein the volume ratio of the coarse-grained inorganic oxide powder A to the total volume of the coarse-grained inorganic oxide powder A and the fine-grained inorganic oxide powder B is 9.5 to 29.0 volume %.

13. The powder for laminated molding according to claim 11 or 12, wherein the D50 (D A 50 and D50 of the microparticle inorganic oxide powder B, i.e. D B 50 Satisfaction D A 50-D B 50≥3.5μm. 14 . The powder for laminated modeling according to claim 8 , wherein D50 of the fine-particle inorganic oxide powder B is 5.0 to 8.0 μm.

15. The powder for laminated molding according to claim 8 or 11, The ratio of D50 to D10 of the coarse-grained inorganic oxide powder A, i.e., D50 / D10, is 1.5 to 3.

5. The ratio of D90 to D10 of the coarse-grained inorganic oxide powder A, ie, D90 / D10, is 4.0 to 7.

0. 16 . The powder for laminated modeling according to claim 8 , wherein the coarse-grained inorganic oxide powder A and the fine-grained inorganic oxide powder B are both spherical in shape. 17 . The powder for laminated modeling according to claim 8 , wherein the coarse-grained inorganic oxide powder A and the fine-grained inorganic oxide powder B are both aluminum oxide.

18. The powder for laminated molding according to claim 17, wherein the bulk density of the powder after compaction at a pressure of 98 MPa is 2.52 to 2.54 g / cm 3 .

19. The powder for laminated modeling according to any one of claims 1 to 3, 8, 9, 11 and 12, which is used in a binder jetting method.

20. A sintered body, which is a sintered body of the powder for laminated modeling according to any one of claims 1 to 3, 8, 9, 11 and 12.

21. A method for manufacturing a binder-injected laminated body, comprising: applying a liquid containing a binder to the laminated modeling powder according to any one of claims 1 to 3, 8, 9, 11 and 12 to form a three-dimensional laminated body.

22. A method for producing a sintered body, comprising: Applying a liquid containing a binder to the powder for laminated molding according to any one of claims 1 to 3, 8, 9, 11 and 12 to form a three-dimensional laminated molding; and The three-dimensional stacked shaped body is sintered.

23. Alumina powder, D10 is 1.0~4.0μm, D50 is 5.5~9.0μm, D90 is 20.0~40.0μm, The volume ratio of particles having a particle size of 16.8 to 60.0 μm is 15.0 to 22.0% by volume.

Citation Information

Patent Citations

  • Material for laminate molding, method of manufacturing cast by powder fixing lamination method and casting mold

    JP2016117069A

  • Ferrite particles for bonded magnet resin composition for bonded magnet and molded products using the same

    CN101345110A

  • Three dimensional printing of cermet or cemented carbide

    CN109311091A

  • Production of photocurable formulation for additive manufacturing

    CN109311759A

  • Powder for lamination molding

    JP2018130835A